First International Conference on Lysophospholipids and Related Bioactive Lipids in Biology and Disease Sponsored by the Federation of American Societies of Experimental Biology - Edward J. Goetzl; Gabor J. Tigyi; Timothy Hla (The Scientific World Journal)
The First International Conference on “Lysophospholipids and Related Bioactive Lipids in Biology and Diseases” was held in Tucson, AZ on June 1014, 2001, under the sponsorship of the Federation of American Societies of Experimental Biology (FASEB). More than 100 scientists from 11 countries discussed the recent results of basic and clinical research in the broad biology of this emerging field. Immense progress was reported in defining the biochemistry of generation and biology of cellular effects of the bioactive lysophospholipids (LPLs). These aspects of LPLs described at the conference parallel in many ways those of the eicosanoid mediators, such as prostaglandins and leukotrienes. As for eicosanoids, the LPLs termed lysophosphatidic acid (LPA) and sphingosine 1-phosphate (S1P) are produced enzymatically from phospholipid precursors in cell membranes and act on cells at nanomolar concentrations through subfamilies of receptors of the G protein–coupled superfamily. The rate-limiting steps in production of LPLs were reported to be controlled by specific phospholipases for LPA and sphingosine kinases for S1P. The receptor subfamilies formerly were designated endothelial differentiation gene-encoded receptors or Edg Rs for their original discovery in endothelial cells. A currently active nomenclature committee at this conference suggested the ligand-based names: S1P1 = Edg-1, S1P2 = Edg-5, S1P3 = Edg-3, S1P4 = Edg-6, and S1P5 = Edg-8; LPA1 = Edg-2, LPA2 = Edg-4, and LPA3 = Edg-7 receptors. Several families of lysophospholipid phosphatases (LPPs) have been characterized, which biodegrade LPA, whereas S1P is inactivated with similar rapidity by both a lyase and S1P phosphatases.